The role of the C8 proton of ATP in the regulation of phosphoryl transfer within kinases and synthetases - Kenyon, Colin P (BioMed Central, 2011)
BACKGROUND: The kinome comprises functionally diverse enzymes, with the current classification indicating very little about the extent of conserved regulatory mechanisms associated with phosphoryl transfer. The apparent K(m )of the kinases ranges from less than 0.4 μM to in excess of 1000 μM for ATP. It is not known how this diverse range of enzymes mechanistically achieves the regulation of catalysis via an affinity range for ATP varying by three-orders of magnitude. RESULTS: We have demonstrated a previously undiscovered mechanism in kinase and synthetase enzymes where the overall rate of reaction is regulated via the C8-H of ATP. Using ATP deuterated at the C8 position (C8D-ATP) as a molecular probe it was shown that the C8-H plays a direct role in the regulation of the overall rate of reaction in a range of kinase and synthetase enzymes. Using comparative studies on the effect of the concentration of ATP and C8D-ATP on the activity of the enzymes we demonstrated that not only did C8D-ATP give a kinetic isotope effect (KIE) but the KIE's obtained are clearly not secondary KIE effects as the magnitude of the KIE in all cases was at least 2 fold and in most cases in excess of 7 fold. CONCLUSIONS: Kinase and synthetase enzymes utilise C8D-ATP in preference to non-deuterated ATP. The KIE obtained at low ATP concentrations is clearly a primary KIE demonstrating strong evidence that the bond to the isotopically substituted hydrogen is being broken. The effect of the ATP concentration profile on the KIE was used to develop a model whereby the C8H of ATP plays a role in the overall regulation of phosphoryl transfer. This role of the C8H of ATP in the regulation of substrate binding appears to have been conserved in all kinase and synthetase enzymes as one of the mechanisms associated with binding of ATP. The induction of the C8H to be labile by active site residues coordinated to the ATP purine ring may play a significant role in explaining the broad range of K(m )associated with kinase enzymes.